Sebaran Spasial Emisi Karbon Dioksida (CO₂) dari Aktivitas Rumah Tangga di Kelurahan Aur Kenali Kota Jambi - Muqorrobin, Fajri; Hadrah, Hadrah; Riyanti, Anggrika; Kalsum, Siti Umi; Kasman, Monik (Universitas Batanghari Jambi, 2026)
This study aims to analyze the magnitude and spatial distribution pattern of carbon dioxide (CO₂) emissions generated from household activities in Aur Kenali Village, Telanaipura District, Jambi City. Emissions were estimated from electricity consumption, LPG usage, transportation activities, and household waste generation. A quantitative approach was applied through questionnaires to representative households. Emission calculations were conducted using standard emission factors. Spatial analysis employed Geographic Information System with the Inverse Distance Weighted (IDW) interpolation method to model emission distribution. The results indicate that electricity and LPG are the largest contributors to household emissions. The IDW map reveals emission concentrations in densely populated residential zones and areas with high economic activity. The study provides spatial information to support local mitigation policies.